Increasing the Role of the Sultan in Local Politics: Case Study of the Role of the Sultan of Tidore in the Policy Making Process for the Special Capital Region of Sofifi in North Maluku Province - M Sahrul Fikri Samson; Syahrul Hidayat (Borong Newinera Publisher, 2024)
This research aims to analyze and identify the increasing role of the sultan in the democratic era in the context of building his role in society and his role as an informal leader in influencing formal institutions. The approach used in this study is a qualitative approach. A qualitative approach was chosen in this research because it is able to explore in depth and detail a social phenomenon and human problem. The results of this research show that in increasing his role, Sultan Husain Syah placed greater emphasis on symbolic roles to build a positive image in society. This increased role then allows him to influence the role of formal institutions by dominating their roles and ideas in a policy-making process. In this case, it is the policy making process for the Special Capital Region of Sofifi in North Maluku Province.